Terpene glucoside production: Improved biocatalytic processes using glycosyltransferases. Issue 4 (9th February 2015) - Schwab, Wilfried; Fischer, Thilo; Wüst, Matthias
<x xml:space="preserve">Abstract</x> Terpenoids are one of the main classes of natural products. In plants, a large fraction of the terpenoids is present as nonvolatile glycosides. The terpene glycosides have attracted much attention as antimicrobials, flavor precursors, and detergents. They are either extracted from plant materials or are synthesized by chemical and biocatalytic methods. Up to now, biotechnological production of terpene glycosides is based on reversed hydrolysis performed by glycosidases. However, this method suffers from low yields as a matter of principle. Recently, the first uridine diphosphate‐glucose:monoterpenol β‐d‐glucosyltransferase (GT) genes were cloned and characterized from grapevine (Vitis vinifera) and kiwi (Actinidia deliciosa). Heterologous expression in Escherichia coli yielded promiscuous GT enzymes that efficiently glucosylated primary monoterpenols, simple alcohols, and phenols. The GT enzymes differed in substrate preference and activity toward their terpenoid substrates. Biotransformation experiments confirmed the applicability of the novel GTs in biocatalytic processes for the production of these novel compounds. In the near future, terpene glucosides will become commercially available for food, cosmetic, and pharmaceutical industry due to improved biocatalytic processes involving GT enzymes.